Cooperative excitonic quantum ensemble in perovskite-assembly superlattice microcavities - Chun Zhou (Nature Portfolio, 2020)
The realization and control many-body quantum states in perovskites would extend their application to ultrafast quantum operation. Here, the authors generate a cooperative quantum state of excitons in a lead halide perovskite quantum dot ensemble and control the ultrafast radiation through optical microcavites.